2023
DOI: 10.3390/biomedicines11061736
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Role of Cell-Free Approaches in SARS-CoV-2-Induced Cytokine Storm—A Powerful Therapeutic Tool for COVID-19 Patients

Abstract: Currently, there is still no effective and definitive cure for the coronavirus disease 2019 (COVID-19) caused by the infection of the novel highly contagious severe acute respiratory syndrome virus (SARS-CoV-2), whose sudden outbreak was recorded for the first time in China in late December 2019. Soon after, COVID-19 affected not only the vast majority of China’s population but the whole world and caused a global health public crisis as a new pandemic. It is well known that viral infection can cause acute resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 174 publications
0
8
0
Order By: Relevance
“…These miRNAs can decrease the production of inflammatory cytokines and minimize cell death by targeting the corresponding 3′-UTRs of multiple mRNAs and TLR pathways such as TLR7/NF-kB signaling. In general, the mechanism of exosomal miRNAs effect on cytokine storm in COVID-19 take place in different ways, the most important of which is to reduce the level of chemokines and pro-inflammatory cytokines through the release of IL-1 receptor agonist, secreting the anti-inflammatory protein TNF-α–stimulated gene 6 protein (TSG-6), and finally, downregulating NF-kB signaling in a TLRs-dependent signaling pathway ( Kiaie et al., 2021 ; Csobonyeiova et al., 2023 ). On the other hand, it has also been shown that the use of miRNA can be effective in controlling HIV infections.…”
Section: Exosomes-tlrs Intraction and Infection Controlmentioning
confidence: 99%
“…These miRNAs can decrease the production of inflammatory cytokines and minimize cell death by targeting the corresponding 3′-UTRs of multiple mRNAs and TLR pathways such as TLR7/NF-kB signaling. In general, the mechanism of exosomal miRNAs effect on cytokine storm in COVID-19 take place in different ways, the most important of which is to reduce the level of chemokines and pro-inflammatory cytokines through the release of IL-1 receptor agonist, secreting the anti-inflammatory protein TNF-α–stimulated gene 6 protein (TSG-6), and finally, downregulating NF-kB signaling in a TLRs-dependent signaling pathway ( Kiaie et al., 2021 ; Csobonyeiova et al., 2023 ). On the other hand, it has also been shown that the use of miRNA can be effective in controlling HIV infections.…”
Section: Exosomes-tlrs Intraction and Infection Controlmentioning
confidence: 99%
“…This enables them to cross the blood-brain barrier, thereby preventing the occurrence of pulmonary embolism following transplantation of MSCs [ 109 ]. Interestingly, MSC-exosomes can be used as nanocarriers to deliver antiviral drugs and anti-inflammatory agents [ 110 ]. Hence, they are regarded as a nanoscale delivery platform for microRNAs, which by nature may target and modify genes associated with the cytokine storm, a severe immune response found in COVID-19 patients [ 111 ].…”
Section: Nano-based Delivery Systems For Mscs/msc-exosomes In Covid-19mentioning
confidence: 99%
“…Specifically, when infection occurs in the body, they are recruited to the damaged site via interactions between chemokines and chemokine receptors [17]. Subsequently, Toll-like receptors (TLRs) on the macrophage surface can recognize pathogens via pathogen-associated molecular patterns (PAMPs), leading to macrophage activation [18,19]. Activated macrophages serve in removing pathogens and cell debris and present antigens to T cells to drive the adaptive immune response [18].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Toll-like receptors (TLRs) on the macrophage surface can recognize pathogens via pathogen-associated molecular patterns (PAMPs), leading to macrophage activation [18,19]. Activated macrophages serve in removing pathogens and cell debris and present antigens to T cells to drive the adaptive immune response [18]. In addition, macrophages are regulated via interactions between multiple cytokines and cytokine receptors on their membranes, resulting in phenotypic changes [20].…”
Section: Introductionmentioning
confidence: 99%